Aquilo que é tecido em conjunto: o ensino como unidade complexa do sistema publicitário em transformação - Cezar, Lara Timm (2021)
With this research we intend to follow the diachronic and evolutionary movement of teaching publicity and advertising, understanding how teaching changes (or remains unmodified) over the years, whether it adapts to the transformations of the advertising system and how it works. For this reason, the changes in the advertising system and the teaching of advertising are the theme of this research. As a starting point, the research problem of this investigation materializes in the following question: how is the diachronic process of teaching advertising developed in view of the reconfigurations of the advertising system? Through this question, we guide our process of exploring the changing movements of education with the intention of considering it part of the advertising system and not using the logic of dichotomous thinking between academia and the market. The general objective of the research is to map the reconfigurations of the advertising system that impact the training of advertising professionals. We use the intention of mapping according to the way we think about research, through our methodological choice: cartography. With an understanding of science not built on the rigidity of models and methods, we perceive this methodology as a path, a path that seeks to build a map that never ends. The research also relies on other methodological resources, such as documentary research and in-depth interviews with professors, students and advertising professional’s alumni and graduates from two universities, one public and the other private. In addition, we formulate some specific objectives, which are: Understand the teaching of advertising as a complex unit of the advertising system; To recognize the reconfigurations of the advertising system; Understand how pedagogical practices are developed with a focus on advertising; We sew these objectives into the concept of complex thinking, through Edgar Morin (2015), when materializing the logic of knowing without fragmenting, of a thought that is not linear and that contemplates the multidimensionality and the complex. Expanding the structure, we have two other axes of research: the advertising system, a term originally coined by Trindade (2017), but which we strongly associate with the complexity of this research, which refers to the entire ecosystem and the practices of the profession, contemplating the academic environment and the marketing; and teaching, bringing the specificities of the training of publicists and publicists, mainly through Marques Filho (2018) and Hansen, Correa and Petermann (2020). As a result of this investigation, we mapped the reconfigurations of the advertising system and analyzed how these transformations impact the formation of publicists and advertisers, through systemic parameters and aspects of complexity.